Learning Discipline On The Learning Outcomes Of Creative And Entrepreneurial Projects Of Students Of Smk Negeri 9 Padang - Ariani, Ulfah; Gusnita, Wiwik; Kasmita, Kasmita; Andriani, Cici (Universitas Negeri Padang, 2025)
This research is based on the low learning outcomes of students' creative projects and entrepreneurship. One of the factors that affect learning outcomes is learning discipline. This study aims to: 1) Describe student learning disciplines, 2) Describe the learning outcomes of creative and entrepreneurial projects, 3) Analyze the influence of learning disciplines on the learning outcomes of creative and entrepreneurial projects. This type of research is quantitative with an Ex Post Facto approach. The population of this study is 224 students in grade XII Culinary at SMK Negeri 9 Padang for the 2024/2025 school year. The sampling technique used was simple random sampling obtained by 70 students. Data collection was carried out by distributing questionnaires directly using a likert scale that has been tested for validity and reliability. The data analysis uses a simple linear regression analysis technique. Based on the results of the study, the results of the t-test have at count of 16.078 > ttable 1.995, then Ha is accepted and Ho is rejected. It can be concluded that: (a) The overall discipline is in the medium category, b) The results ofCreative and Entrepreneurship Projects are in the low category. The results of the study show that there is a positive and significant influence between learning disciplines on the learning outcomes of creative projects and entrepreneurship of students.